Estudo do efeito do laser de baixa potência sobre a inflamação pulmonar induzida por isquemia e reperfusão intestinal - Lima, Flávia Mafra de (2013)
The systemic inflammation caused by ischemia and reperfusion (I/R-i) is characterized by generating , in exaggerated amounts of proinflammatory cytokines such as TNF- α , IL -1β IL- 6 and NO. The injury that occurs in various organs after intestinal I/R-i is generally related to the occurrence of microvascular injury, increased plasma extravasation increased expression of adhesion molecules, recruitment and activation of inflammatory cells (mainly neutrophils). The anti-inflammatory effects of low-level laser (LLL) is known in many diseases, however, the mechanisms of its action are not yet well understood. The objective of this study is to describe the effect of low level laser on pulmonary inflammation in an experimental model of ischemia and reperfusion in order to investigate the possible mechanisms involved in these effects .Therefore, we divided the study into three stages: 1st) The goal was to evaluate the effect of laser in reactivity cholinergic dysfunction and release of inflammatory mediators in the lung after I/R-i 2nd) The objective was to assess whether the laser treatment could modulate the proinflammatory mediators and anti -inflammatory drugs in acute lung inflammation induced by I / Ri. 3rd) was conducting a study dose response model of lung inflammation induced by I / Ri in mice Methods: Wistar rats (150 - 200g) and C57/BL6 mice (20 - 25g) from the animal house of the Nove de Julho University. Each experimental group consisted of 5 animals each, as follows: naive group (baseline), sham (fake - operated), I/R-i, I/R + LBP -intestinal lymph in the region. The animals were anesthetized intraperitoneally with Ketamine / Xylazine (20 mg/kg-100 mg/kg) and after laparotomy and desvicerização intestinal ischemia was induced by clamping the superior mesenteric artery for 45 minutes. In the period after reperfusion (2 hours) the animals were anesthetized and sacrificed by exsanguination through the abdominal aorta. The animals were irradiated with a diode laser with a power of 30 mW and a wavelength of 660 nm irradiating an area of 0785 cm2 with a dose of 5.4 J in rats and (0.78 , 2.37 , 3.9, 5.8J ) in mice. Results Step 1: We note that, although laser treatment reduces edema and myeloperoxidase expression, it does not happen in all periods of reperfusion. This was also observed in the expression of ICAM- 1. But at the same time reducing TNF- α and iNOS laser increases the expression of IL -10 in the lungs of rats subjected to I / Ri Step 2: The results indicate that the laser reduces edema, MPO expression and TNF - α in the lungs when compared with control groups. laser increased the expression of IL - 10 in the lungs and 3rd stage: in mouse model, laser has also shown to be effective in reducing the concentration indirect neutrophils in the lung tissue at doses (2.37, 3.9, 5.8 J) and reduced mRNA expression and protein synthesis of (IL - 1β, TNF -α, IL - 6, IL - 10) Conclusion: we conclude that treatment with low level laser therapy is effective for lung inflammation induced by I / Ri at the doses studied. The dose that best submitted result was 3.9 J. Our results showed that the laser has reduced inflammatory cell migration and edema. Regarding the expression of iNOS laser has also shown to be effective in reducing its expression , and this indicates an effect of laser treatment on the reactivity of the trachea , since the I / Ri reactivity of the trachea is directly related to the concentrations of NO and IL-10. Regarding the expression of mRNA and protein synthesis of pro- inflammatory mediators (IL- 1, IL- 6 and TNF- α) laser was shown to reduce these values , and enhance protein synthesis in IL-10